2009
DOI: 10.1007/s10530-009-9653-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in vegetation coincident with annual grass invasion negatively impacts sprint velocity of small vertebrates

Abstract: Sagebrush ecosystems in the intermountain west of the United States are being threatened by conversion to the non-native grass, cheatgrass (Bromus tectorum). The dramatic shift in the physical structure of vegetation coincident with cheatgrass invasion likely has negative impacts on animal communities, yet these structural impacts have not been well-studied. In a previous study, dense cheatgrass stems reduced sprint velocity for the flattened, wide-bodied desert horned lizard (Phrynosoma platyrhinos). Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 60 publications
3
52
0
Order By: Relevance
“…Cluttered habitats prove difficult for maintenance of a straight path of travel and forward speed during movement, requiring a behavioral repertoire to negotiate obstacles (Rieder et al, 2010;Garber and Pruetz, 1995;Tucker and McBrayer, 2012). Quickly maneuvering on or over obstacles can play a vital role in predator evasion in complex habitats (Kohlsdorf and Navas, 2007;Tucker and McBrayer, 2012).…”
Section: Performance and Behavior With And Without Obstaclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cluttered habitats prove difficult for maintenance of a straight path of travel and forward speed during movement, requiring a behavioral repertoire to negotiate obstacles (Rieder et al, 2010;Garber and Pruetz, 1995;Tucker and McBrayer, 2012). Quickly maneuvering on or over obstacles can play a vital role in predator evasion in complex habitats (Kohlsdorf and Navas, 2007;Tucker and McBrayer, 2012).…”
Section: Performance and Behavior With And Without Obstaclesmentioning
confidence: 99%
“…Many lizard and rodent species have lower escape speeds in dense vegetation compared with open areas (Vasquez et al, 2002;Schooley et al, 1996;Goodman, 2009;Vanhooydonck and Van Damme, 2003). Species utilizing bipedal running may be able to exploit habitat types with uneven substrata because of the increases in visual perception and/or by reaching their maximum speed more quickly (Rieder et al, 2010;Djawdan and Garland, 1988;Rocha-Barbosa et al, 2008;Kohlsdorf and Biewener, 2006). Because two obstacles create the same negative performance effect on stride characteristics and velocity, bipedalism is likely only beneficial when negotiating a single obstacle (Fig.…”
Section: Performance and Behavior With Multiple Obstaclesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, work at Portal indicates that a precipitation-driven closing of habitats caused a shift in the body size distribution of granivorous small mammals from a mean individual size of 73.4 to 33.7 g over a 24-y time period (3). Reider et al (35) have shown that, although cheatgrass significantly reduces sprint speed for all species, this is disproportionately so for larger saltatory species. Furthermore, Lightfoot et al (36) have recently shown that species affiliated with natural annual grasslands in the Chihuahuan desert exhibit greater reproductive potential, and thus faster population responses to changes in resources, than shrub-affiliated species.…”
Section: Have Human Activities Yielded An Energetically Novel Ecosystem?mentioning
confidence: 99%
“…In order to elicit maximal running performance, the animals in that study were pursued with a padded yardstick. As previously discussed, Rieder et al (2010) did not thoroughly account for three potentially important factors: a) non-linear running path (such that measurements of velocity as assessed by raceway distance/time rather than path distance/time would potentially underestimate velocity), b) the magnitude (type, frequency, etc.) of the "motivation tactic," or pursuit with the padded yardstick, each animal received, and c) the possibility of habituation to a habitat patch and therefore loss of the detrimental effects imposed by the grass on running performance over time.…”
Section: Locomotion In Veldt Grassmentioning
confidence: 99%